2021
DOI: 10.3390/f13010037
|View full text |Cite
|
Sign up to set email alerts
|

Soil Bacterial and Fungal Community Responses to Throughfall Reduction in a Eucalyptus Plantation in Southern China

Abstract: In subtropical plantations in southern China, how soil microbial communities respond to climate change-induced drought is poorly understood. A field experiment was conducted in a subtropical Eucalyptus plantation to determine the impacts of 50% of throughfall reduction (TR) on soil microbial community composition, function, and soil physicochemical properties. Results showed that TR reduced soil water content (SWC) and soil available phosphorus (AP) content. TR significantly altered 196 bacterial operational t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
4
7
0
Order By: Relevance
“…We further discovered that the major functional genes were all metabolism-related functions. This result was in line with the reports of Lin et al (2022), who found that metabolism played an extremely pivotal role in the soil of Eucalyptus plantations. Furthermore, no significant differences were found in bacterial functional groups between the topsoil and subsoil (Supplementary Tables S2, S3), indicating that soil depth might not be the main factor affecting bacterial function.…”
Section: Effects Of Fertilization On the Function Of Soil Microbial C...supporting
confidence: 93%
See 2 more Smart Citations
“…We further discovered that the major functional genes were all metabolism-related functions. This result was in line with the reports of Lin et al (2022), who found that metabolism played an extremely pivotal role in the soil of Eucalyptus plantations. Furthermore, no significant differences were found in bacterial functional groups between the topsoil and subsoil (Supplementary Tables S2, S3), indicating that soil depth might not be the main factor affecting bacterial function.…”
Section: Effects Of Fertilization On the Function Of Soil Microbial C...supporting
confidence: 93%
“…These results believed that long-term fertilization reduced bacterial species and richness via aggravating soil acidification (Curtin et al, 1998;Yao et al, 2014;Chen et al, 2015). We also found that bacterial diversity gradually decreased with the deepening of the soil layer, which was consistent with previous studies that showed lower bacterial diversity in the subsoil of the Eucalyptus plantation than in the topsoil (Lin et al, 2022). The reason for this result might be due to less accumulation of elemental contents (e.g., N and P) in the deeper soil (Wang et al, 2017).…”
Section: Effects Of Fertilization On the Diversity And Composition Of...supporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the activity and growth of plants and soil microbes are affected by water availability (Engelhardt et al, 2021). Congruent with previous reports (Zhao et al, 2017;Su et al, 2020;Lin et al, 2022), this study showed that TR significantly reduced SWC in the rainy season. For other soil physicochemical properties, their contents were almost all reduced in the rainy season relative to those in the dry season.…”
Section: Discussionsupporting
confidence: 81%
“…The RDA and mental test results showed that soil and plant properties were significantly associated with bacterial and fungal communities of the five karst tiankengs ( Figure 6 ; Supplementary Table 1 ). SWC has been widely demonstrated to construct soil bacterial and fungal communities ( Kaisermann et al, 2015 ; Long et al, 2021 ; Lin et al, 2022 ). Soil moisture content can directly affect the survival activity of microbes, and affect microbial growth by indirectly regulating the distribution of soil nutrients ( Clark et al, 2009 ; Manzoni et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%